1
$\begingroup$

If $0\lt a \le 1, s\gt 1,$ define $\zeta(s,a)=\sum (n+a)^{-s}$.

Show that this series converges absolutely for $s \gt 1$ and prove that

$$\sum_{h=1}^k \zeta(s,\frac{h}{k})=k^s\zeta (s)\ \ \ \text{if} \ k=1,2,...,$$

where $\zeta(s)=\zeta(s,1)$ is the Riemann zeta function.

I know that the series converges absolutely for $s \gt 1$ from the p-series test.

$\sum_{h=1}^k \zeta(s,\frac{h}{k})=\sum_{h=1}^k \sum_{n=0}^\infty \frac{k^s}{(kn+h)^s}=k^s \sum_{n=0}^\infty \sum_{h=1}^k \frac{1}{(kn+h)^s}$.

I am stuck here. How can I show that this last summation equals $k^s \sum_{n=0}^\infty \frac{1}{(n+1)^s}$?

I would greatly appreciate any help.

$\endgroup$
1
$\begingroup$

We have $$\sum_{h=1}^{k}\zeta\left(s,\frac{h}{k}\right)=\sum_{h=1}^{k}\sum_{n\geq0}\frac{k^{s}}{\left(nk+h\right)^{s}}=k^{s}\sum_{n\geq0}\sum_{h=0}^{k-1}\frac{1}{\left(nk+h+1\right)^{s}}. $$ Now note that every positive integer $a $ can be expressed in the form $a=nk+h $ for some $n\in\mathbb{N} $ and $h\in\left[0,k-1\right] $. It's simply $a\textrm{ mod }k $. Then $$k^{s}\sum_{n\geq0}\sum_{h=0}^{k-1}\frac{1}{\left(nk+h+1\right)^{s}}=k^{s}\sum_{n\geq0}\frac{1}{\left(n+1\right)^{s}}=k^{s}\zeta\left(s\right). $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.